Studi Sikap Konsumen dalam Berbelanja Online di Jakarta dengan Kepercayaan sebagai Variabel Mediasi - Ferditan, Jesslyn; Ruslim, Tommy Setiawan (Universitas PGRI Yogyakarta, 2024)
The aim of this research is to determine the influence of relative advantage and EWOM on consumer attitudes towards online shopping in Jakarta with trust as a mediating variable. The technique used in this research is non-probability sampling with a purposive sampling approach. The respondents sampled in this research were 172 consumer respondents who had shopped online and lived in Jakarta. The data analysis method in this research uses the SmartPLS program version 4.1.0.0. The research results show that relative advantage and EWOM have a positive and significant influence on trust and attitudes, trust has a positive and significant influence on attitudes, trust can mediate the positive and significant influence between relative advantage and EWOM on attitudes.